Strategi Pemasaran Beras Organik di Desa Bareng Kecamatan Bareng Kabupaten Jombang - Nurul Annisa Sholehah; Mohamad Nasirudin; M Abdu Naim (Program Studi Agribisnis, 2021)
The purpose of this research to identify any internal and eksternal factors which can be a strengths, weakness, opportunities and threats of marketing organic ricein the Banjarsari farmer group in the Bareng village Bareng sub-district Jombang district. This research uses the SWOT analysis method obtained from the matrik IFAS-EFAS, SWOT quadrant and SWOT matrik. The respondents of this research are head of the Banjarsari farmer group and six member who are members of the Banjarsari farmer group. Based on the results of the IFAS matrik analysis research, the total score is 2,29. EFAS matrik analysis result are 2,67. After knowing the results of the IFAS/EFAS matrik than determining the SWOT quadrant. Quadrant results show the Banjarsari farmer group is in quadrant one (agresif). Namely showing a very favorable situation for the Banjarsari farmer group becausa it has opportunities and strengths so that they can take advantage of existing opportunities. With this research it is hoped that the Banjarsari farmer group can expand market share, maintain the quality of organic rice and improve product packaging.